Perilaku makan sebelum dan selama pandemi covid-19 pada kelompok remaja dan dewasa di Indonesia - Fillah Fithra Dieny; Firdananda Fikri Jauharany; A. Fahmy Arif Tsani; Choirun Nissa (AcTion: Aceh Nutrition Journal, 2021)
The COVID-19 pandemic impacts lifestyle changes, one of which is the eating behavior of people. The research aims to examine changes in eating behavior before and during the COVID-19 pandemic among adolescents and adult groups in Indonesia. A cross-sectional study on 563 subjects, with the subject's inclusion criteria, namely living in Indonesia, aged 12-55 years, willing to participate in the research by filling in informed consent and filling out a questionnaire via an online google form. The data obtained were grouped based on variables before and after the pandemic, then tested the normality of the data. Bivariate analysis used the Wilcoxon text because the data were not normally distributed. As a result, there was an increase in the subject's breakfast habits and frequency of eating. Subjects experienced changes in eating habits, namely an increase in the frequency, variety, and portion of consumption of animal protein, vegetable protein, vegetables, and fruit between before and during the COVID-19 pandemic (p <0,001). In addition, the habit of consuming fluids, supplements, and spices also experienced a significant increase, while the pattern of snacking decreased between before and during the pandemic (p <0,001). In conclusion, there were differences in eating behavior: breakfast habits, dietary variations, consumption of animal and vegetable protein, vegetables, fruits, fluids, supplements, spices, and snacking patterns outside the home between before and during the pandemic in the subject